A note yet unsung - Alexander, Tamera (Alexander, Tamera. Belmont Mansion novel, 2017)
A master violinist trained in Vienna, Rebekah Carrington manages to wheedle her way into an audition with the newly formed Nashville Philharmonic. But women are "far too fragile and frail" for the rigors of an orchestra, and Rebekah's hopes are dashed because the conductor bows to public opinion. Nationally acclaimed conductor Nathaniel Tate Whitcomb is Nashville's new orchestra leader, and despite a strange buzzing and recurring pain in his head, he is determined to finish composing his symphony before the grand opening of the city's new opera hall--and before his father dies. As Tate's ailment worsens, he believes that Rebekah can help him finish his symphony. But how do you win back a woman's trust when you've robbed her of her dream? --